ChemInform Abstract: β‐Selective Mannosylation with a 4, 6‐Silylene‐Tethered Thiomannosyl Donor. Issue 31 (5th August 2014) - Heuckendorff, Mads; Bendix, Jesper; Pedersen, Christian M.; Bols, Mikael
Abstract New conformationally restricted mannopyranoside donors react with various acceptors with high β‐selectivity under various reaction conditions, among other using simple NIS/TfOH procedure.